DEFENSE OFFSETS DALAM PROGRAM PENGEMBANGAN PESAWAT TEMPUR KF-21 BORAMAE TAHAP II INDONESIA DENGAN KOREA SELATAN - Fathurrahman, Gesa Atras; Saeri, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study examines the implementation of defense offsets in the joint development of the KF-21 Boramae fighter jet between Indonesia and South Korea. Using qualitative methods and theoretical frameworks of international cooperation and defense diplomacy, the research focuses on three aspects: (1) Indonesia’s offset policy under Law No. 16/2012, (2) the dynamics of the KF-21 Phase II project (2012-2023), and (3) the project’s significance for Indonesia’s national interests. Findings reveal that while Indonesia secured 15% industrial participation via direct offsets (technology transfer, human resource training, and component manufacturing), the initial 20% target was unmet due to U.S. technology restrictions under the Defense Technology Security System (DTSS). Rational actor model analysis indicates Indonesia’s commitment to continue the project stems from strategic calculations, including defense industrial capacity building, international reputation enhancement, and reduced reliance on arms imports. The study recommends strengthening legal offset frameworks and diversifying partners to mitigate future geopolitical risks. Keywords: Defense offsets, KF-21 Boramae, technology transfer, defense industry, Indonesia-South Korea cooperation